1993
DOI: 10.1002/ajp.1350300207
|View full text |Cite
|
Sign up to set email alerts
|

Body size and fatness of free‐living baboons reflect food availability and activity levels

Abstract: We used morphometric techniques and isotope-labeled water to investigate the influence of abundant, accessible food and resultant low activity levels on body size and fatness in free-living adolescent and adult baboons as compared to animals in the same population that experienced more typical, wild-feeding conditions. Females that had access to abundant food from a nearby garbage dump averaged 16.7 kg body mass, 50% more than their wild-feeding counterparts in adjacent home ranges. Little of the difference wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
164
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(192 citation statements)
references
References 25 publications
(5 reference statements)
8
164
1
Order By: Relevance
“…While this is most common in captive primates (e.g. in zoos), significant levels of obesity have also been observed in free-ranging populations of baboons (Altmann et al 1993) and macaque monkeys on the island of Cayo Santiago off the coast of Puerto Rico (Schwartz et al 1993). In both cases this was associated not with natural foods, but with access to garbage dumps (baboons) and the management practice of supplementing the natural diet with primate chow (macaques).…”
Section: Wildlife Conservationmentioning
confidence: 99%
“…While this is most common in captive primates (e.g. in zoos), significant levels of obesity have also been observed in free-ranging populations of baboons (Altmann et al 1993) and macaque monkeys on the island of Cayo Santiago off the coast of Puerto Rico (Schwartz et al 1993). In both cases this was associated not with natural foods, but with access to garbage dumps (baboons) and the management practice of supplementing the natural diet with primate chow (macaques).…”
Section: Wildlife Conservationmentioning
confidence: 99%
“…Until the development of DXA, the only means to precisely measure total body fat mass in non-human primates were the isotope method (Altmann et al 1993), and dissection to extract as much fat as possible (McFarland and Zihlman 1997;Hayama et al 1998). The development of DXA has allowed total body fat mass to be accurately measured in 10 minutes or less.…”
Section: Fat Accumulation In Japanese Macaquesmentioning
confidence: 99%
“…Altmann et al (1993) reported that baboons in troops relying on garbage for food have 23.2% fat mass whereas, wild baboons, which do not depend on garbage, have as low as 1.9%. They also showed that females tend to carry more fat than males.…”
Section: Obesity and Leanness In Japanese Macaquesmentioning
confidence: 99%
See 1 more Smart Citation
“…An example more directly relevant to foraging is a study is of three troops of baboons in the Amboseli Naional Park, Kenya [77]. One troop had for many years incorporated the use of menu items from a dumpster at a tourist lodge, while the other two troops were exclusively wild-feeding.…”
Section: Relevance To Obesitymentioning
confidence: 99%